Analysis of the Quality of Mixed Coconut Shell Waste Briquettes with Various Biomass Additives as Alternative Fuels - Yusraida Khairani Dalimunthe; Sugiatmo Kasmungin; Listiana Satiawati; Thariq Madani; Teuku Ananda Rizky (Journal of Earth Energy Science, Engineering, and Technology, 2021)
The purpose of this study was to see the best quality of briquettes from the main ingredient of coconut shell wastewith various biomass additives to see the calorific value, moisture content, ash content, and volatile mattercontent of the biomass mixture. Furthermore, further research will be carried out specifically to see the quality ofbriquettes from a mixture of coconut shell waste and sawdust. The method used in this research is to conduct aliterature study of various literature related to briquettes from coconut shell waste mixed with various additivesspecifically and then look at the best quality briquettes produced from these various pieces of literature. As forwhat is determined as the control variable of this study is coconut shell waste and as an independent variable,namely coffee skin waste, rice husks, water hyacinth, Bintaro fruit, segon wood sawdust, coconut husk, durianskin, bamboo charcoal, areca nut skin, and leather waste. sago with a certain composition. Furthermore, thispaper also describes the stages of making briquettes from coconut shell waste and sawdust for further testing ofthe calorific value, moisture content, ash content, volatile matter content on a laboratory scale for furtherresearch. From various literatures, it was found that the highest calorific value was obtained from a mixture ofcoconut shell waste and bamboo charcoal with a value of 7110.7288 cal / gr and the lowest calorific value wasobtained from a mixture of coconut shell waste and sago shell waste with a value of 114 cal / gr, then for the valueThe highest water content was obtained from a mixture of coconut shell waste and rice husk with a value of37.70% and the lowest water content value was obtained from a mixture of coconut shell waste 3.80%, then for thehighest ash content value was obtained from a mixture of coconut shell waste and coffee skin with a value of20.862% and for the lowest ash content value obtained from a mixture of coconut shell and Bintaro fruit waste,namely 2%, and for the highest volatile matter content value obtained from a mixture of coconut shell and coconuthusk waste with a value of 33.45% and for the value of volatile matter levels The lowest was obtained from amixture of coconut shell waste and sago skin waste with a value of 33 , 45%.